Photoelectron spectroscopy as a probe of intramolecular vibrational dynamics in electronically excited toluene - Green, Alistair Malcolm (2011)
Intramolecular vibrational energy redistribution (IVR) is a commonly-observed phenomenon whereby vibrational energy can be transferred between different parts of a polyatomic molecule. This process has profound implications for the understanding of chemical reactivity. In this work, IVR is studied in the S1 electronic state of toluene using time-resolved and frequency-resolved techniques. Both experiments are based upon laser photoelectron spectroscopy in the collision-free environment of a molecular beam.